Enhanced Solubility Through Particle Size Control, Modification of Crystal Behavior, and Crystalline Form Changes in Solid Dispersion of Nifedipine - Jung, Ju young; Il Shin, Kwang; Lee, Minseon; Song, Myeongkwan; Kwon, Soonjo (Biotechnology and bioprocess engineering, 2022)
The purpose of this study was to investigate the selectivity of polymers and the suitability of spray drying to enhance nifedipine solubility. Nifedipine alone or in combination with polymers was dissolved in a mixed solvent of methylene chloride and ethanol. The hydrophilic polymers used were PVP K-30, HPMC, HPMCP, Eudragit, and HPMCAS. Each solid dispersion was prepared using a laboratory spray dryer. The spray-dried solid dispersants were characterized by SEM, DSC, and XRPD analysis, and dissolution tests compared the dissolution rates of nifedipine solid dispersants and nifedipine. The results showed that all spray-dried solid dispersions were in an amorphous form. Dissolution tests were performed at pH 1.2 (artificial gastric juice) and pH 6.8 (artificial intestinal juice) to evaluate solid dispersion solubility. The solid dispersion containing HPMC showed a notably enhanced dissolution rate under both pH conditions. Interestingly, HPMCP and HPMCAS showed almost no enhancement of dissolution behavior at pH 1.2, but a significant increase (10 times or higher) over that of the pure polymer at pH 6.8. Solubility enhancement of poorly soluble drugs differs markedly among the polymers used for spray drying. From the results, HPMCP and HPMCAS are suitable as carriers for drugs with poor solubility that require acid resistance.